Assessment of the nutritional condition of patients with inflammatory bowel disease on admission: A comparison between ulcerative colitis and Crohn disease - ARAKAWA, Tetsuo; SHIMOTANI, Yuko; TSUKADA, Sadanobu; MOMOKI, Chika; YAMAGAMI, Hirokazu; HAYASHI, Fumikazu; WATANABE, Kenji; KAMATA, Noriko; SOGAWA, Mitsue; HABU, Daiki (Jomyaku Keicho Eiyo, 2012)
[OBJECTIVE] We evaluated the nutritional condition of patients with active inflammatory bowel disease (IBD) on admission so that the nutrition support team (NST) could provide them appropriate nutritional therapy. [METHODS] We measured anthropometric parameters, determined body composition by bioelectrical impedance analysis (BIA), performed biochemical assessments of blood, and performed subjective global assessment (SGA) of the nutritional status of IBD patients on admission. [RESULTS] Our results showed that typically, the nutritional conditions of patients with active IBD on admission were very poor. In particular, the nutritional condition of patients with ulcerative colitis (UC) was worse than that of patients with Crohn disease (CD), because patients with UC had greater active inflammation, severe gastrointestinal symptoms, hypermetabolic disorders, and shortage of food intake. [CONCLUSION] Although it might be commonly thought that patients with UC require lesser nutritional support than patients with CD, patients with active UC on admission had poorer nutritional conditions than those of CD patients. Thus, patients with active CD on admission require appropriate nutritional support by the NST.